Combinatorial Strategies for the Induction of Immunogenic Cell Death - Bezu, Lucillia; Gomes-da-Silva, Ligia C.; Dewitte, Heleen; Breckpot, Karine; Fucikova, Jitka; Spisek, Radek; Galluzzi, Lorenzo; Kepp, Oliver; Kroemer, Guido (Frontiers in Immunology, 2015)
The term “immunogenic cell death” (ICD) is commonly employed to indicate a peculiar instance of regulated cell death (RCD) that engages the adaptive arm of the immune system. The inoculation of cancer cells undergoing ICD into immunocompetent animals elicits a specific immune response associated with the establishment of immunological memory. Only a few agents are intrinsically endowed with the ability to trigger ICD. These include a few chemotherapeutics that are routinely employed in the clinic, like doxorubicin, mitoxantrone, oxaliplatin and cyclophosphamide, as well as some agents that have not yet been approved for use in humans. Accumulating clinical data indicate that the activation of adaptive immune responses against dying cancer cells is associated with improved disease outcome in patients affected by various neoplasms. Thus, novel therapeutic regimens that trigger ICD are urgently awaited. Here, we discuss current combinatorial approaches to convert otherwise non-immunogenic instances of RCD into bona fide ICD.